Hendrik Verwoerd and the Leipzig School of Psychology in 1926 (Historia, 2021)
This article looks into the stay of Hendrik Verwoerd in Leipzig, Germany, in 1926. Allegations of an ideological influence by German nationalism on Verwoerd have often been repeated in the historical literature, but were never substantiated by evidence from the archives. The Psychological Institute at the University of Leipzig, where Verwoerd studied, was politically the most conservative and nationalist among the three universities which the young scholar from Stellenbosch visited - the others were Hamburg and Berlin. Nevertheless, no ideological influence on Verwoerd could be found in the available evidence from archives in South Africa and Germany, but certainly the scientific influence of German psychology on Verwoerd the academic cannot be denied. Verwoerd's main objective in going to Germany was to become acquainted with the latest trends in international psychology. He studied with the Leipzig psychologists Felix Krueger, Hans Volkelt, an expert on child psychology, and Otto Klemm, a specialist in applied psychology. His interest focused mainly on developmental psychology, characterology and ethnic psychology (Völkerpsychologie), which can be traced to the lasting influence of Wilhelm Wundt, the founding father of modern psychology in Germany. Whereas Verwoerd's interest in different fields of psychology stemmed from his long lasting involvement with the "poor white problem" in South Africa, Völkerpsychologie could possibly have exerted a scientific influence on his later perceptions of racial and cultural differences that fed into apartheid.  Hierdie artikel handel oor die verblyf van Hendrik Verwoerd, in 1926, in Leipzig, Duitsland. Bewerings van 'n ideologiese invloed van Duitse Nasionalisme op Verwoerd kom herhaaldelik voor in die historiese literatuur maar dit is nog nooit onderskraag deur argivale bewyse nie. Die Psigologiese Instituut aan die Universiteit van Leipzig, waar Verwoerd gestudeer het, was polities die mees konserwatiefste, die ander twee was Hamburg en Berlyn, wat hy besoek het. Desnieteenstaande kon geen ideologiese invloed op Verwoerd gevind word in die argiewe in Suid-Afrika en Duitsland nie maar die wetenskaplike impak van die Duitse psigologie op hom kan nie ontken word nie. Die belangrikste rede waarom Verwoerd Duitsland besoek het was vir blootstelling aan die mees resente tendense in die internasionale psigologie. In Leipzig het hy onder die psigoloog Felix Krueger, die kinder psigoloog, Hans Volkelt en 'n spesialis in toegepaste psigologie, Otto Klemm, gestudeer. Sy belangstelling was in die algemeen gefokus op ontwikkelings psigologie, karakterologie en etniese psigologie (Völkerpsychologie) wat teruggevoer kan word na die bepalende invloed van Wilhelm Wundt, die vader van moderne psigologie in Duitsland. Waar Verwoerd se belangstelling in die verskillende vertakkinge van die psigologie gespruit het uit sy lang betrokkenheid by die "armblanke vraagstuk" in Suid-Afrika kon die Völkerpsychologie dalk 'n wetenskaplike invloed uitgeoefen het op sy latere persepsies aangaande ras en kultuur verskille wat op hul beurt weer apartheid beinvloed het.
Keywords: frikaner nasionalisme; History of psychology; Hendrik Verwoerd; Apartheid